Evaluasi Kinerja Sistem Irigasi Tetes Berbasis Gravitasi dengan Menggunakan Limbah Plastik - Rahman, Khaidir; Novitasari, Ervi; Jamaluddin, Jamaluddin; Ilham, Ilham (Jurnal Pendidikan Teknologi Pertanian, 2024)
Watering plants by farmers or urban residents who like gardening generally still uses traditional methods such as buckets or hoses directly. This method is less effective because it relies on human power, takes a lot of time, and produces uneven air distribution in each planting medium, so it is necessary to develop sprinklers that can solve this problem. This research aims to design a gravity drip irrigation device and conduct performance tests. The form of this research is engineering research, research data is obtained from the results of equipment testing and observations of the air distribution process and coefficient of variation analysis. The data analysis method used is quantitative with a descriptive statistical approach. As a result of the research, it was obtained that the coefficient of variation value for the emitter of output channel 1 had an overall average value per minute of 0.13%. output channel 2 every minute is 0.11% and the coefficient of variation in the water distribution reservoir has an overall average value every minute of 0.12%. The average percentage value of the uniformity level at each minute is in the medium category but close to the good category.